2019
DOI: 10.1080/08870446.2019.1673895
|View full text |Cite
|
Sign up to set email alerts
|

A theory-based intervention delivered by an online social media platform to promote oral health among Iranian adolescents: a cluster randomized controlled trial

Abstract: Objective: Based on the Health Action Process Approach, we tested the efficacy of a theory-based program using an online social media platform (Telegram) to promote good oral hygiene behaviour among Iranian adolescents. Design: A three-arm randomized-controlled trial design was used, consisting of an adolescent only intervention group (A group; n ¼ 253), an adolescent and mother intervention group (A þ M group; n ¼ 260), and a control group (n ¼ 278). Main outcome measures: Psychosocial variables, toothbrushin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 42 publications
2
67
0
Order By: Relevance
“…Regarding the interventions described in the studies, we found that apps ( n = 9; Li et al 2016; Zotti et al 2016; Alkadhi et al 2017; Marchetti et al 2018; Alkilzy et al 2019; Zotti et al 2019; Deleuse et al 2020; Scheerman, Hamilton, et al 2020; Scheerman, van Meijel, et al 2020) and text messages (Eppright et al 2014; Jejurikar et al 2014; Bowen et al 2015; Abdaljawwad 2016; Cozzani et al 2016; Jadhav et al 2016; Iqbal et al 2017; Kumar et al 2018; Araujo et al 2019) were the most commonly used. Apps were combined with other strategies, such as educational messages (Li et al 2016; Scheerman, Hamilton, et al 2020), reinforcement messages (Li et al 2016; Marchetti et al 2018), reminders (Li et al 2016; Deleuse et al 2020; Scheerman, van Meijel, et al 2020), push notifications (Alkadhi et al 2017; Scheerman, van Meijel, et al 2020), videos (Li et al 2016; Alkadhi et al 2017; Scheerman, Hamilton, et al 2020; Scheerman, van Meijel, et al 2020), and selfies to evaluate plaque control (after using a plaque-disclosing tablet; Zotti et al 2016; Scheerman, Hamilton, et al 2020; Scheerman, van Meijel, et al 2020), or they were wirelessly connected to electric toothbrushes (Alkilzy et al 2019; Deleuse et al 2020). Some studies with apps allowed gamification activities (Zotti et al 2016; Alkilzy et al 2019; Zotti et al 2019).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Regarding the interventions described in the studies, we found that apps ( n = 9; Li et al 2016; Zotti et al 2016; Alkadhi et al 2017; Marchetti et al 2018; Alkilzy et al 2019; Zotti et al 2019; Deleuse et al 2020; Scheerman, Hamilton, et al 2020; Scheerman, van Meijel, et al 2020) and text messages (Eppright et al 2014; Jejurikar et al 2014; Bowen et al 2015; Abdaljawwad 2016; Cozzani et al 2016; Jadhav et al 2016; Iqbal et al 2017; Kumar et al 2018; Araujo et al 2019) were the most commonly used. Apps were combined with other strategies, such as educational messages (Li et al 2016; Scheerman, Hamilton, et al 2020), reinforcement messages (Li et al 2016; Marchetti et al 2018), reminders (Li et al 2016; Deleuse et al 2020; Scheerman, van Meijel, et al 2020), push notifications (Alkadhi et al 2017; Scheerman, van Meijel, et al 2020), videos (Li et al 2016; Alkadhi et al 2017; Scheerman, Hamilton, et al 2020; Scheerman, van Meijel, et al 2020), and selfies to evaluate plaque control (after using a plaque-disclosing tablet; Zotti et al 2016; Scheerman, Hamilton, et al 2020; Scheerman, van Meijel, et al 2020), or they were wirelessly connected to electric toothbrushes (Alkilzy et al 2019; Deleuse et al 2020). Some studies with apps allowed gamification activities (Zotti et al 2016; Alkilzy et al 2019; Zotti et al 2019).…”
Section: Resultsmentioning
confidence: 94%
“…The median number of participants per study was 126.3 (range, 34 to 478), with most studies in the field of orthodontics including adolescents and young adults (Abdaljawwad 2016; Iqbal et al 2017). Four studies pertained to preventive dentistry in children (Alkilzy et al 2019; Zotti et al 2019) or adolescents (Marchetti et al 2018; Scheerman, Hamilton, et al 2020), 2 to the field of general dentistry (Jadhav et al 2016; Araujo et al 2019), and 1 to patients with periodontal disease (Williams et al 2018). Most patients were recruited from dental practices (either at university clinics or private practices), and few studies recruited a sample from university students (Jadhav et al 2016) or high school students (Marchetti et al 2018; Scheerman, Hamilton, et al 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Include a manipulation check, e.g., the subjective feeling of being recovered (Binnewies et al, 2009) to ascertain the effectiveness of the intervention and control group treatment. (Fjeldsoe et al, 2020;Lester et al, 2010), influenced self-motivation through social media communication (Scheerman et al, 2020), and promoted health and well-being through gameplay (Schakel et al, 2020). Reminder functions on smart-phones, apps, or smartwatches can support interventions, and allow them to be tailored to entrepreneurs' current level of recovery engagement (Eatough et al, 2016).…”
Section: Collect Demographic Datamentioning
confidence: 99%
“…1,3,6,7,16 The use of social media in oral health has also been recommended. 17 As a result, the "Senyuman Indah Milik Semua" Program (SIMSP) or "Beautiful Smile for All" Program was introduced in 2019 which improvised on the existing POHP. In the SIMSP, apart from DTs, preschool teachers and parents are included in school and home oral health activities.…”
Section: Introductionmentioning
confidence: 99%